A review of the literature on corporal punishment in The Bahamas, with an emphasis on its use in schools - Fielding, William J.; Ballance, Virginia C. (International Journal of Bahamian Studies, 2020)
This review of the literature concerning corporal punishment arising from The Bahamas enables us to identify several strands: (1) corporal punishment is an historically accepted method of controlling children which only recently has been called into question; (2) school teachers have typically seen corporal punishment as a useful classroom management tool; (3) there has been unease about its use in schools which has resulted in its regulation; (4) more recently, there has been evidence of the awareness of the long-term negative effects of corporal punishment; and (5) the rise of social media has made corporal punishment and its potential abuses visible to a wider audience. These strands appear to have woven together to move the country in a direction of outlawing corporal punishment, at least in schools.